The Routledge Handbook of Literacy Studies - Rowsell, Jennifer; Pahl, Kate (New York : Routledge, 2015)
'The Routledge Handbook of Literacy Studies offers a comprehensive view of the field of language and literacy studies. With forty-three chapters reflecting new research from leading scholars in the field, the handbook pushes at the boundaries of existing fields and combines with related fields and disciplines to develop a lens on contemporary scholarship and emergent fields of inquiry. The Handbook is divided into eight sections:The foundations of literacy studiesSpace-focused approachesTime-focused approachesMultimodal approachesDigital approachesHermeneutic approachesMaking meaning from the everyday Co-constructing literacies with communitiesThis is the first handbook of literacy studies to recognise new trends and evolving trajectories together with a focus on radical epistemologies of literacy. The Routledge Handbook of Literacy Studies is an essential reference for undergraduate and postgraduate students and those researching and working in the areas of applied linguistics and language and literacy.'--
Includes bibliographical references and index.
Keywords: Modality (Linguistics); Literacy -- Social aspects -- Cross-cultural studies; Technological literacy; Mass media in education